All at once: how electrochemistry can be used to design and access multiple compositions in a single sample. Issue 43 (25th October 2017) - Ruffo, Vitor A.; Crisci, Alexandre; Chatenet, Marian; Camara, Giuseppe A.
Abstract : A library of PtRh compositions is simultaneously obtained by electrodeposition in a diffusion-controlled cell. This approach enables to perform compositional studies in a single piece of substrate and open new perspectives of studies in heterogeneous catalysis and electrocatalysis. Abstract : A library of binary PtRh thin-film electrocatalysts was obtained by potentiostatic co-electrodeposition of Pt 4+ and Rh 3+ on a gold wire in a capillary cell, the capillary separating on the one hand the Pt 4+ compartment and on the other hand the Rh 3+ compartment. More specifically, this capillary cell enables to hinder the mobility of the ions from the one compartment to the other, thereby creating a continuous gradient of concentrations of Pt 4+ and Rh 3+ in the solution along the gold wire; as a result, the surface of the gold wire substrate witnesses crossed gradients of Pt 4+ and Rh 3+ during the electrodeposition, and countless PtRh compositions can be generated on the surface of a single sample. The feasibility of the protocol was confirmed by electron probe microanalysis and sections of the film (with lengths of 1 mm) were subsequently accessed by cyclic voltammetry. The results demonstrate the potential of this approach to perform compositional studies in a single piece of substrate and open new perspectives of studies in catalysis and electrocatalysis with a relatively low-cost and time-saving approach.